Project-Based Learning Model Oriented Towards Creative Character in Poetry Text Learning for 10th Grade High School Students - Fufu Fadilah; Abdul Rozak; Dede Endang Mascita (PT Inovasi Pratama Internasional, 2024)
This research is entitled